THE IMPACT OF USING MULTIMEDIA IN IMPROVING ENGLISH VOCABULARY ACQUISITION AMONG PRIMARY SCHOOL STUDENTS - Ach. Munawi Husein; Fitria Meisarah; Didi Sudrajat (CV. ADIBA AISHA AMIRA, 2024)
The use of multimedia technology in teaching English has become one of the most powerful methods to improve students' vocabulary skills at the primary school level. The study conducted in this research uses the literature study method. The results show that multimedia can create a much more interesting and varied learning experience, which in turn facilitates the recall and comprehension of new English words. Through the dynamic interaction provided by multimedia, students can see and hear words in various contexts, which helps to enrich their understanding. Furthermore, the use of multimedia can accelerate the teaching- learning process and increase students' motivation to learn English. Multimedia content is often designed with interesting visual and audio elements and educational games that encourage learning. These features not only make learning more fun, but also create a positive competitive atmosphere, so that students become more actively involved in learning and experience faster vocabulary improvement. However, the successful utilisation of multimedia in English vocabulary learning requires effective integration by teachers and sufficient technological support. Appropriate teaching strategies, along with continuous evaluation of student progress, are key to optimising learning outcomes. Thus, multimedia serves not only as a teaching aid, but also as a core component that can enrich the learning experience and improve student achievement at the primary school level